SOCIAL LIFE YOUNG AGE IN THE FAMILY WEDDING PREPARATION IN NAGARI PERSIAPAN SITOMBOL KECAMATAN PADANG GELUGUR KABUPATEN PASAMAN - -, Deswita - (Pendidikan Geografi, 2014)
Humans need other humans in his life because he could not live alone perfectly. No human being can live without help from others. Human dependence with each other due to the limitations of human being has to be able to meet their own needs. But beyond that limitation he bona fide human strengths of the other. There are things that are not owned or are not able to be done by others, but for other men, he can and is able to do so, then with complementary humans are capable of overcoming their needs. This study aimed to obtain information, analyze and discuss data on socio-economic conditions of the family marries a young age in villages Padang District gelugur Preparation Sitombol Pasaman. This type of research is descriptive. The study population was all couples who marry at a young age sitombol preparation villages numbering 149 people. The sample of respondents with proportional random sampling technique and 30% of the sample is determined so that the sample of this study is the young age of 45 married couples. The instrument used in this study is a questionnaire or a questionnaire. data analysis using a percentage formula. The results of this research find: 1) The level of education of respondents in the study area category low 41 (91.1%) with an average primary school and junior high. Based on the above it is clear that education was very important in creating prosperity and the happiness of an individual. Education is very important in every area of life. 2) The level of low income respondents category which are under provincial minimum wage of Rp 1.49 million / month. In this case the public revenue very important role in the welfare of the family. The higher the level of family income more needs can be fulfilled, because the income was not only used for the primary alone but other needs can also be met. 3) The level of the respondents health is normal category. It can be seen from the type of food consumed by a family member and nutritional conditions as well as a family treatment. So is the attention to toddlers, this family generally give only breast milk until the 1-year-old toddler.